Short-term fertility intentions among married women in depok city: a cross-sectional study based on the theory of planned behavior - Hilma Amrullah; Istiqlaliyah Muflikhati; Lilik Noor Yuliati (Lentera Negeri, 2026)
The decline in fertility in urban areas of Indonesia highlights the importance of understanding psychosocial determinants of reproductive decision-making. This study examined short-term fertility intention among married women in Depok City using the Theory of Planned Behavior framework. A quantitative cross-sectional design was employed involving 155 married women aged 19–35 years with no children or one child who completed a structured questionnaire. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicated that attitude, subjective norm, and perceived behavioral control (PBC) were positively associatedwith effects on fertility intention (R² = 0.285). Among the TPB constructs, PBC showed the largest standardized coefficient (β=0.346, 95% CI: 0.205-0.487), followed by subjective norm (β=0.279, 95% CI: 0.126-0.432) and attitude (β=0.185, 95% CI: 0.060- 0.310). These findings suggest that fertility intentions in this urban context are shaped not only by personal evaluations but also by perceived control and social influences. In this context, fertility decision-making reflects considerations of readiness and perceived ability to manage reproductive, economic, and life demands. The study highlights the relevance of psychosocial factors in fertility intentions and may provide insights for reproductive health programs and family guidance and counseling practices in context urban setting. Findings should be interpreted within the context of the study’s purposive sample and cross-sectional design.